Highly Sensitive Fluorescent Biosensor Based on Acetylcholinesterase and Carbon Dots–Graphene Oxide Quenching Test for Analytical and Commercial Organophosphate Pesticide Detection - Gaviria, Maria I.; Barrientos, Kaory; Arango, Juan Pablo; Cano, Juan B.; Peñuela, Gustavo A. (Frontiers in Environmental Science, 2022)
Chlorpyrifos formulations are the most used in Colombia and other countries for crop protection, and their presence has been proven in many water sources. The application of nanomaterials, including carbon quantum dots (CD), can significantly improve the performance of optical biosensors for quick and accurate detection of these pesticides. In this work, naturally fluorescent and non-toxic CD were conjugated with acetylcholinesterase (AChE) as a bioreceptor, to produce a fluorescent biosensor. This system was modulated with graphene oxide (GO), showing a fluorescence recovery in the presence of the pesticide. The biosensor was evaluated for the detection of pure chlorpyrifos (CPF), profenofos (PF), and a commercial formulation called Lorsban®. A limit of detection (LOD) as low as 0.14 ppb and 2.05 ppb for chlorpyrifos and Lorsban® respectively was obtained. Profenofos did not show any recovery with this system at the evaluated concentrations. The system also showed a good selectivity in the presence of proteins (BSA) and other organic substances (Glucose) usually present in drinking water. The specificity was also evaluated against cypermethrin and methomyl commercial formulations showing minimal interference. To the best of our knowledge, this is one of the few works reporting the detection of commercial pesticide formulations with promising results.